Modelling the Pathways of Leadership, Workload, and Teacher Stress to Performance: A Structural Equation Analysis in West Tanjung Jabung, Indonesia - Leni Rahmadani; Robi Hendra; Akhmad Habibi (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2025)
This study aims to analyse the direct and indirect effects of leadership style, teacher stress, and workload on teacher performance, with job satisfaction as a mediating variable. Using a quantitative approach and Partial Least Squares Structural Equation Modelling (PLS-SEM), data were collected from 303 teachers in Tungkal Ilir District, West Tanjung Jabung Regency, Indonesia, through a structured Likert-scale questionnaire. The results reveal that leadership style and workload significantly enhance job satisfaction, positively affecting teacher performance (β = 0.330; p < 0.05). Job satisfaction mediates the influence of leadership and workload on performance, highlighting its central role in teacher management. The model demonstrates strong predictive power (R² = 81.6% for teacher performance). These findings suggest that supportive leadership and fair workload distribution can transform workplace challenges into positive motivation. The study provides practical insights for educational policymakers and school leaders to design management strategies that foster teacher satisfaction and performance, particularly in rural education contexts.